PENGARUH KOMPETENSI PEGAWAI, KOMUNIKASI, LINGKUNGAN KERJA DAN ETOS KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN POLONIA - Anthonius Yonathan Pardede (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The formulation of the problem in this study are: Does Employee competency partially influence employee productivity at the Medan Polonia Tax Service Office, Does communication have a partial effect on employee work productivity, does the work environment partially affect employee work productivity ?, Does the work ethic partial effect on employee work productivity? Does the employee competence, communication, work environment and work ethic jointly affect the employee work productivity in the Polonia Medan Primary Tax Office ?, Research Objectives Are: To determine the effect of employee competency partially on employee work productivity, to determine the effect of employee communication partially on employee work productivity, to know the effect of work facilities partially on employee work productivity, to determine the effect of work ethic in a way rial on employee work productivity, to determine the effect of employee competence, communication, work environment and work ethic simultaneously on employee work productivity. Data analysis techniques used are descriptive analysis and deductive analysis. The results showed that there was a significant influence between employee competence on employee work productivity, because according to the results of the analysis of t count t-table (1.758 1.67) at n = 59 with a significance level of 95%. There is a significant effect between communication on employee work productivity, because according to the results of the analysis of t count t-table (3.183 1.67) at n = 59 with a significance level of 95%. There is a significant influence between the work environment on employee work productivity, because according to the results of the analysis of t count t-table (1.672 1.671) at n = 59 with a significance level of 95%. There is a significant influence between work ethic on employee work productivity, because according to the results of the analysis of tcount t-table (2,029 1.67) at n = 59 with a significant level. F-count value F table (41,324 2.54) together (multiple) there is a positive and significant effect on employee competence, communication, work environment and work ethic on employee work productivity. Thus the hypothesis proposed is accepted.